ECCO essential requirements for quality cancer care: Oesophageal and gastric cancer. (February 2018) - Allum, William; Lordick, Florian; Alsina, Maria; Andritsch, Elisabeth; Ba-Ssalamah, Ahmed; Beishon, Marc; Braga, Marco; Caballero, Carmela; Carneiro, Fatima; Cassinello, Fernando; Dekker, Jan Willem; Delgado-Bolton, Roberto; et al.
Highlights: ECCO essential requirements for quality cancer care (ERQCC) are position papers on delivering high-quality. Each paper focuses on a cancer type, in this case oesophageal-gastric cancer. Oesophageal-gastric cancers are highly demanding and complex to treat. High-quality care can only be a carried out in specialised units or centres. The essential, multidisciplinary details for such centres are set out by the ERQCC expert group. Abstract: Background: ECCO essential requirements for quality cancer care (ERQCC) are checklists and explanations of organisation and actions that are necessary to give high-quality care to patients who have a specific type of cancer. They are written by European experts representing all disciplines involved in cancer care. ERQCC papers give oncology teams, patients, policymakers and managers an overview of the elements needed in any healthcare system to provide high quality of care throughout the patient journey. References are made to clinical guidelines and other resources where appropriate, and the focus is on care in Europe. Oesophageal and gastric: essential requirements for quality care: Oesophageal and gastric (OG) cancers are a challenging tumour group with a poor prognosis and wide variation in outcomes among European countries. Increasing numbers of older people are contracting the diseases, and treatments and care pathways are becoming more complex in both curative and palliative settings. High-quality care can only be a carried out in specialised OG cancer units or centres which have both a core multidisciplinary team and an extended team of allied professionals, and which are subject to quality and audit procedures. Such units or centres are far from universal in all European countries. It is essential that, to meet European aspirations for comprehensive cancer control, healthcare organisations implement the essential requirements in this paper, paying particular attention to multidisciplinarity and patient-centred pathways from diagnosis, to treatment, to survivorship. Conclusion: Taken together, the information presented in this paper provides a comprehensive description of the essential requirements for establishing a high-quality OG cancer service. The ERQCC expert group is aware that it is not possible to propose a 'one size fits all' system for all countries, but urges that access to multidisciplinary units or centres must be guaranteed for all those with OG cancer.